(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: Green tea (Camelia sinensis L.) contains flavonoids consisting of Epigallocatechin gallate (EGCG) which functions as whitening, anti-acne, antioxidant, anti-inflammatory. Previous studies have shown that EGCG with a concentration of 6% is the optimum concentration in cream formulations (Widyaningrum, 2015b). Phase One Clinical Test was conducted to determine the safety of cream preparations with irritation as a benchmark and continued to test its effectiveness as a whitening cream on 20 respondents aged 17-45 years. Material and Methods: The research method employed was the Open Test. The results of the study for 21 days after applying the EGCG anti-acne cream were assessed using a mexa-meter and self-assessment. Result: The erythema assessment showed that the preparation did not cause irritation in the absence of erythema and for the melanin assessment, the results were not significant with p Value 0.376 (<0,05) with no changes in the melanin index. The results of the irritation test were supported by the findings of self-assessment which revealed that all self-assessment parameters were not significant and there was no irritation (p 0,317). Conclusion: Based on the results of the study, it could be concluded that EGCG whitening cream did not cause irritation for 21 days. The results of the melanin test formula for this whitening cream preparation were able to provide a skin whitening effect. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 902-906